Resting-State Functional Connectivity Predicts Emotional Conflict Control - Song Xue; Wei Xu (International Journal of Psychotherapy Practice and Research, 2019)
Emotional conflict control refers to the ability to select task-relevant emotional information and ignore task-irrelevant emotional distractors. Previous fMRI studies provide some evidence about brain structure and function related to emotional conflict control. Yet, the underlying resting-state functional connectivity was largely unknown. Here, this is the first study to explore the resting-state functional connectivity related to emotional conflict. According to the literature which used the whole-brain analysis to investigate the key brain area associated with emotional conflict, we select the amygdala (AMY) as the seed region. We then investigated the association between emotional conflict and functional connectivity between amygdala (AMY) and another brain region in a large sample. We found the emotional conflict effect was positively correlated with functional connectivity strength between AMY (the seed ROI) and right supplementary motor area (SMA). This finding implied that the functional connectivity between AMY and SMA was linked to emotional conflict and that AMY was the key region which plays a crucial role in emotional conflict.
Keywords: Resting state